2022
DOI: 10.1186/s12985-022-01891-2
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Post-COVID syndromes: a new perspective

Abstract: Most COVID-19 patients recovered with low mortality; however, some patients experienced long-term symptoms described as “long-COVID” or “Post-COVID syndrome” (PCS). Patients may have persisting symptoms for weeks after acute SARS-CoV-2 infection, including dyspnea, fatigue, myalgia, insomnia, cognitive and olfactory disorders. These symptoms may last for months in some patients. PCS may progress in association with the development of mast cell activation syndrome (MCAS), which is a distinct kind of mast cell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 203 publications
(212 reference statements)
1
36
0
5
Order By: Relevance
“…Proposed underlying mechanisms related to the development and manifestation of post-COVID syndrome can include (1) viral persistence upon initial infection of host cells by SARS-CoV-2, (2) cellular damage due persistent hyperinflammation, (3) immunologic aberrations caused by molecular mimicry, epitope spreading, bystander activation, or superantigen, and (4) hemostatic changes, predominantly characterized by coagulation abnormalities [ 23 , 24 , 25 , 26 , 27 , 28 ]. Some of these mechanisms and abnormal or misdirected drivers are displayed in Figure 1 and discussed in more detail below.…”
Section: Pathogenesis Of Post-covid Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Proposed underlying mechanisms related to the development and manifestation of post-COVID syndrome can include (1) viral persistence upon initial infection of host cells by SARS-CoV-2, (2) cellular damage due persistent hyperinflammation, (3) immunologic aberrations caused by molecular mimicry, epitope spreading, bystander activation, or superantigen, and (4) hemostatic changes, predominantly characterized by coagulation abnormalities [ 23 , 24 , 25 , 26 , 27 , 28 ]. Some of these mechanisms and abnormal or misdirected drivers are displayed in Figure 1 and discussed in more detail below.…”
Section: Pathogenesis Of Post-covid Syndromementioning
confidence: 99%
“…Several investigators have observed pulmonary and gastrointestinal SARS-CoV-2 reservoirs that can persist for up to four months [ 25 , 29 ]. Moreover, in a recent autopsy study on 44 patients, persistent SARS-CoV-2 RNA was detected outside the respiratory tract in multiple anatomic sites, including the brain, as late as 230 days following onset of COVID-19 symptoms [ 30 ].…”
Section: Pathogenesis Of Post-covid Syndromementioning
confidence: 99%
“…Additionally, tryptase released by mast cells causes vascular barrier failure, lung fibrosis, and airway inflammation and encourages the spread of SARS-CoV-2 infection [21] . MCAS caused by SARS-CoV-2 may elevate the incidence of developing severe acute COVID-19 and chronic post-COVID-19 diseases [9] . Afrin et al [14] reported that MCAS targeted therapy can lessen the severity of the disease as soon as the development of a COVID-19 disease is identified or suspected.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 postmortem lung biopsies in SARS-CoV-2 infections patients exhibit an enormously elevated number of mast cells, indicating that SARS-CoV-2 infection may have attracted mast cells to the alveolar septa [8] . Post-COVID syndrome may progress in association with the development of mast cell activation syndrome (MCAS) [9] .…”
Section: Introductionmentioning
confidence: 99%
“…A large body literature gave evidence that SARS‐CoV‐2 through activation of toll‐like receptor 4 (TLR4) and nuclear factor κ B (NF‐κB) trigger release of pro‐inflammatory cytokines like TNF‐α 5,71,72 . TNF‐α stimulates opening of Ca 2+ channels in ER through activation of IP3R, which in turn increase cytosolic Ca 2+ by activation of membrane store operated Ca 2+ channels 73 .…”
Section: Role Of Ryanodine Receptors and Dantrolene In Covid‐19mentioning
confidence: 99%